Use of half-generation PAMAM dendrimers (G0. 5–G3. 5) with carboxylate end-groups to improve the DACHPtCl2 and 5-FU efficacy as anticancer drugs - Camacho, Cláudia (2021)
The DACHPtCl2 compound (trans-(R,R)-1,2-diaminocyclohexanedichloroplatinum(II)) is a potent anticancer drug with a broad spectrum of activity and is less toxic than oxaliplatin (trans-l-diaminocyclohexane oxalate platinum II), with which it shares the active metal fragment DACHPt. Nevertheless, due to poor water solubility, its use as a chemotherapeutic drug is limited. Here, DACHPtCl2 was conjugated, in a bidentate form, with half-generation PAMAM dendrimers (G0.5–G3.5) with carboxylate end-groups, and the resulting conjugates were evaluated against various types of cancer cell lines. In this way, we aimed at increasing the solubility and availability at the target site of DACHPt while potentially reducing the adverse side effects. DNA binding assays showed a hyperchromic effect compatible with DNA helix’s disruption upon the interaction of the metallodendrimers and/or the released active metallic fragments with DNA. Furthermore, the prepared DACHPt metallodendrimers presented cytotoxicity in a wide set of cancer cell lines used (the relative potency regarding oxaliplatin was in general high) and were not hemotoxic. Importantly, their selectivity for A2780 and CACO-2 cancer cells with respect to non-cancer cells was particularly high. Subsequently, the anticancer drug 5-FU was loaded in a selected metallodendrimer (the G2.5COO(DACHPt)16) to investigate a possible synergistic effect between the two drugs carried by the same dendrimer scaffold and tested for cytotoxicity in A2780cisR and CACO-2 cancer cell lines. This combination resulted in IC50 values much lower than the IC50 for 5-FU but higher than those found for the metallodendrimers without 5-FU. It seems, thus, that the metallic fragment-induced cytotoxicity dominates over the cytotoxicity of 5-FU in the set of considered cell lines.